Dutch Municipalities are Becoming Greener: Some Political and Institutional Explanations - Raymond Gradus; Elbert Dijkgraaf (Tinbergen Institute, 2017)
This paper analyzes whether Dutch municipalities became greener between 1999 and 2014 by investigating whether they implement different unit-based pricing systems. Based on their incentive, systems are ranged from green ('weight') to less green ('volume'), or not green ('flat rate'). In one-third of the municipalities, shifts took place, with 83 percent becoming greener and 17 percent less green. Political fragmentation (measured in three ways) plays a key role in explaining these shifts. There is less evidence for political motivation. Particularly, Conservative Liberals are not in favor of unit-based pricing, whereas Social Liberals are in favor. In addition, municipalities in rural and shrinking areas are more in favor of unit-based pricing.
Keywords: D72; H76; H79; 330; local government; unit-based waste pricing; greener; less green; ideological motivation